Forest rehabilitation requires fire prevention and community involvement - Toma, T.; Oka, T.; Marjenah; Fatawi, M.; Mori, T. (Center for International Forestry Research, 2001)
In East Kalimantan, Indonesia drought is frequently followed by fire. The eastern part of Kutai Regency is susceptible to large-scale wildfires during severe droughts related to strong El Niño Southern Oscillation (ENSO) events as shown by the 1982-83 and 1997-98 fires. Since the 1982-83 forest fire, many trials have been conducted to rehabilitate the burned forests. However, the 1998 fires burned both natural and rehabilitated forests in East Kalimantan. It is to be expected that severe droughts related to strong ENSO events and subsequent wildfires will occur again in the near future. At the time of the next severe ENSO event, people should remember that extremely severe drought is likely to recur early in the following year. Without effective fire prevention, the rehabilitated areas will be burned again and the rehabilitation process will not have enough time to reach completion. To rehabilitate burned forests and grasslands as well as to conserve the remaining natural forests, it is important that community-based initiatives are undertaken to reduce potential fire sources and to enhance fire management activities. Clear benefits to the local community should be introduced and announced to the local people before and during forest rehabilitation